Letterland beyond ABC - Holt, Lisa; Wendon, Lyn (Letterland International Ltd. Cambridge, England, 2007)
Introduces 21 of the popular digraphs in full colour scenes. This work presents the story logic for each new sound and children are encouraged to search the scenes looking for the target sound in initial, medial and final positions in words. It helps in phonemic awareness and vocabulary development.